Membangun Kemampuan Pemecahan Masalah dan Kreativitas Mahasiswa Melalui Penugasan Pembuatan Alat Peraga Program Linear - Hanifah Hanifah (University of Bengkulu, 2020)
The aims of this study were to determine the results of the posttest, the ability to solve problems, the advantages of making props Liner Program (Prolin) by students. The subjects of the study were the 64 students from 3rd semester of Mathematics Education - Bengkulu University, 2019/2020 Academic Year who took the Mathematics Economics course. The instruments used were posttest sheets, and questionnaires. The method used were implementing post-test; checking the answers based on Polya's stages which consist of: 1) Understanding Problems; 2) Make a Plan; 3) Carry out a Plan; and 4) Evaluation. We concluded that the average post-test score was 83.52 Students' problem solving abilities were: 1) 93.75% were able to understand the problem: 2) 85.94% were able to make a plan: 3) Stage of doing the plan: 78.125% were able to determine the cut point; 70.31% were able to paint graphics; 76.56% were able to determine the final grade; 65.63% were able to calculate the value of the objective function; 67.19% were able to conclude; 4) only 53.125% were able to evaluate. Questionnaire results: 33.96% had difficulty where 11.11% could not make a table, 50.00% could not make a model, 11.11% could not determine the intersection of the graph, 16.67% could not paint the graph, 16.67% cannot calculate the objective function correctly. Students recall Prolin's material when: 66.04% prepare papers, 15.09% of friends present, 18.87% make props, 1.89% of friends present props, 5.66% were unable to remember until posttest. The advantages of making teaching aids for students were: the material is easy to understand, learning becomes fun, develops creativity and innovation so that the props become interesting, as a provision for teaching Prolin that is easy to understand and fun.